INFORMATIONAL TRANSFORMATION OF CHARACTERISTICS OF SURFACE HETEROGENEITY IN CASTING AND METALLURGY - A. P. Markov; S. S. Sergeev; I. M. Strotskij; A. G. Starovoitov; E. M. Patuk (Литьë и металлургия)
The models and structures of informational transformation of characteristics of the surface heterogeneity of the geometric bodies elements in casting and metallurgy are examined.